Kinetics and Mechanism of Oxidation of 2-Methoxyethanol and 2-Ethoxyethanol by Potassium Ferrate - Huan Shan, Jin; Ying Zhang, Ji; Xia Shen, Hai; Qian Wang, Xiao (Asian Journal of Chemistry, 2010)
The kinetics of oxidation of 2-methoxyethanol and 2-ethoxyethanol by potassium ferrate(VI) in alkaline liquids at a constant ionic strength has been studied spectrophotometrically in the temperature range of 293.2-313.2 K. The reaction shows first order dependence on potassium ferrate(VI), first order dependence on each reductant. The observed rate constant (kobs) decreases with the increase in [OH–], the reaction is negative fraction order with respect to [OH–]. A plausible mechanism is proposed and the rate equations derived from the mechanism can explain all the experimental results. The rate constants of the rate-determining step and the activation parameters are calculated.